E-090 Intraoperative MRI for endovascular coiling of intracranial aneurysms: a single center experience. (23rd July 2022) - Yan, Y; Shankar, J; Kaderali, Z; Chowdhury, T
Abstract : Intraoperative magnetic resonance imaging system (iMRIS) surgical theatre is a highly integrated operating room with an iMRI designed originally for brain tumor surgery. Its use in neurointerventional procedures, particularly in the setting of endovascular coiling of intracranial aneurysms, have not been discussed in the literature to date. We present our initial experience about the safety and feasibility of intraoperative MRI to assess post operative complications and provide baseline imaging post coiling of intracranial aneurysms. In our early experience, a total of 15 patients underwent intra-operative MRI with MRA to assess post coiling status of the intracranial aneurysm. The iMRI is an advantageous tool which can be integrated into neurointerventional workflow resulting in early post preprocedural feedback and potentially reduced post-operative hospital stay. Disclosures: Y. Yan: None. J. Shankar: None. Z. Kaderali: None. T. Chowdhury: None.